Kajian Morfologi Dan Perubahan Fungsi Alun-Alun Utara Keraton Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The North Alun-Alun of Yogyakarta palace, situated at the convergence of the sacred space of the keraton with secular life, are the setting for the keraton's ceremonies and the 'little people's' interaction with the sovereign. In its course of history, the North Alun-Alun has been transformed from functioning as the private open space of palace to a public open space. The present research shows phenomena of the functional and physical transition/change in the north Alun-Alun. The decline of space quality, environment, and sense of place , the decrease of the cultural value, and commercial tendency are parts of the north AIun-Alun's problems. To answer the growth and change of spatial pattern and function of north Alun-Alun were morphologically analized by exploring of various data of spatial pattern and function and its staging transformation processes into present, and identifying the changes. It followed by explorative activities to find fact in the field and then analized to find the results in accordance with the purpose of this study. The results are : first, there are three types of change in the north Alun-Alan such as (a) not significant changeover, (b) form and function changeover by decreasing and increasing, (c) totally change over, second, it has transformed from a private open space of palace to a public open space, third, difference perception and context of the north Alun-Alun purpose comes into physical and function change.